2017
DOI: 10.17221/172/2017-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Compounds in Stem Juice from Banana

Abstract: Nguyen D., Nováková A., Spurná K., Hričko J., Phung H., Viktorová J., Stránská M., Hajšlová J., Ruml T. (2017): Antidiabetic compounds in stem juice from babana grown in natural and greenhouse. Czech J. Food Sci., 35: 407-413.The stem juices from Musa × paradisiaca L. banana plants cultivated in their original natural habitat in Vietnam and those cultivated in a greenhouse in the Czech Republic were investigated for the presence of phytochemicals with antidiabetic potency. Respective bioactivities of these phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The extracts were diluted with methanol to concentrations from 0.001 mg/mL to 0.1 mg/mL. To 20 µL of the diluted extract, we added 60 µL of PBS and 10 µL of the α-amylase with a concentration of 0.8 mg/mL and incubated at room temperature (20 • C for 10 min) according to [23]. Afterwards, 10 µL of substrate CNPG3 (2-chloro-p-nitrophenyl-α-D-maltotrioside, 6.6 mg/mL) was added; after that, the absorbance (400 nm) was immediately recorded in 1 min intervals for 10 min.…”
Section: Antidiabetic Activity Assaymentioning
confidence: 99%
“…The extracts were diluted with methanol to concentrations from 0.001 mg/mL to 0.1 mg/mL. To 20 µL of the diluted extract, we added 60 µL of PBS and 10 µL of the α-amylase with a concentration of 0.8 mg/mL and incubated at room temperature (20 • C for 10 min) according to [23]. Afterwards, 10 µL of substrate CNPG3 (2-chloro-p-nitrophenyl-α-D-maltotrioside, 6.6 mg/mL) was added; after that, the absorbance (400 nm) was immediately recorded in 1 min intervals for 10 min.…”
Section: Antidiabetic Activity Assaymentioning
confidence: 99%
“…According to (Zaini, et al, 2022), bioactives found in natural foods have a significant potential for use in the food sector or as therapeutic agents for other metabolic illnesses. (Kalita, et al, 2016;Nguyen, et al, 2017;Indrawati, et al, 2022;Abdel-Naime et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ferulic acid was successfully determined among other bioactive compounds in stem juices from banana plants using a tandem high-resolution mass spectrometry (UHPL-HRMS/MS) method. An investigation into variations in the occurrence of potentially antidiabetic compounds revealed signi cant differences in the concentration of ferulic acid based on the origin of the bananas, underscoring the in uence of growth conditions on its presence (Nguyen et al 2017). Phenolic compound pro ling in various banana varieties was also conducted through two analytical methods, HPLC-ESI-HR-MS and HPLC-DAD.…”
Section: Resultsmentioning
confidence: 99%